The mixed-state Hall conductivity of single-crystal films Nd2–xCexCuO4+δ (x = 0.14) - Shelushinina, N.G.; Harus, G.I.; Charikova, T.B.; Petukhov, D.S.; Petukhova, O.E.; Ivanov, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
The magnetic-field dependencies of the longitudinal and Hall resistivity of the electron-doped compounds Nd2–xCexCuO4+δ in underdoped region (x = 0.14) were investigated. It was established experimentally a strong magnetic field dependence of the Hall conductivity, σxy(B) = C – b/B, in the region of magnetic fields corresponding to a transition from superconducting to resistive state. The observed feature can be explained with the sum of contributions of the quasiparticles and moving Abrikosov vortices into Hall effect in a mixed state of type-II superconductor.